2022
DOI: 10.1364/oe.452422
|View full text |Cite
|
Sign up to set email alerts
|

Transmission enhancement of a half-wave wall under extreme angles by synergy of double lorentz resonances

Abstract: The a half-wave wall is usually adopted as the transparent window for electromagnetic (EM) waves ranging from microwave to optical regimes. Due to the interference nature, the bandwidth of the half-wave wall is usually quite narrow, especially under extreme angles for TE-polarized waves. It is usually contradictory to expand the bandwidth and to keep high transmission. To overcome this contradiction, we propose to extend the transmission bandwidth of half-wave walls under extreme angles by introducing Lorentz-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Moreover, figure 6(e) presents the power flow at f 1 . It is shown that the EM waves pass through the plate without obvious deflection at the upper and lower interfaces, which proves that the impedance of the metasurface-embedded plate and air matches well at f 1 [39].…”
Section: Design and Analysismentioning
confidence: 68%
“…Moreover, figure 6(e) presents the power flow at f 1 . It is shown that the EM waves pass through the plate without obvious deflection at the upper and lower interfaces, which proves that the impedance of the metasurface-embedded plate and air matches well at f 1 [39].…”
Section: Design and Analysismentioning
confidence: 68%
“…Previously, metasurface technology was used to improve the radio‐frequency (RF) transmission efficiency of substrates. [ 2,11–17 ] However, some designs are single‐polarized and only improve the transmission efficiency of TE‐polarized waves without considering the TM polarization. [ 2,14,15 ] In ref.…”
Section: Introductionmentioning
confidence: 99%
“…[ 2,11–17 ] However, some designs are single‐polarized and only improve the transmission efficiency of TE‐polarized waves without considering the TM polarization. [ 2,14,15 ] In ref. [17], the single‐fold symmetry the metasurface structure may suffer from severe polarization mismatch in real communication scenarios.…”
Section: Introductionmentioning
confidence: 99%